2009
DOI: 10.1021/jf8031167
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibition of Foodborne and Pathogenic Bacteria by Conjugated Linoleic Acid

Abstract: The influence of conjugated linoleic acid (CLA) on the growth of some foodborne and pathogenic bacteria was examined. A potassium salt of CLA (CLA-K) was tested against three Gram-positive strains ( Bacillus cereus , Staphylococcus aureus , and Streptococcus mutans ) and five Gram-negative strains ( Pseudomonas aeruginosa , Salmonella typhimurium , Vibrio parahemolyticus , Klebsiella pneumoniae , and Proteus mirabilis ). CLA-K-mediated growth inhibition was evident for all tested strains, particularly the Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The SEM, TEM, and Raman spectroscopy images indicate that zinc oxide nanoparticles may damage the bacterial cell membrane resulting in loss of intracellular components and eventually the death of cells [43]. In our current study, the morphological changes in E. coli O157:H7 caused by the action of copper and lactic acid are somehow similar to the observations made by previous studies [3942]. The study of bacterial populations in laboratory medium did not show any effect of copper alone against E. coli O157:H7.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The SEM, TEM, and Raman spectroscopy images indicate that zinc oxide nanoparticles may damage the bacterial cell membrane resulting in loss of intracellular components and eventually the death of cells [43]. In our current study, the morphological changes in E. coli O157:H7 caused by the action of copper and lactic acid are somehow similar to the observations made by previous studies [3942]. The study of bacterial populations in laboratory medium did not show any effect of copper alone against E. coli O157:H7.…”
Section: Discussionsupporting
confidence: 87%
“…In another study observed by TEM, bacteria treated with essential oils (Eos) showed formation of blebs, coagulation of cytoplasmic constituents, damaged cell structure, and were devoid of cytoplasmic material [38]. Similarly, SEM study of bacterial cells showed damage to the outer membrane and morphological changes of the cells when treated with eicosapentaenoic acid (EPA) and potassium salt of conjugated linoleic acid (CLA-K) [39, 40]. Bacterial cells exposed to carvacrol and thymol showed the disintegration of outer membrane of E.coli O157:H7 and Salmonella Typhimurium.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we revealed in vitro that LC + mcra could competitively exclude the growth and adhesive activity of both ST and EHEC [20] and at meanwhile, suppress their vital virulence gene factors. Moreover, though effectiveness of probiotics in combatting enteric bacterial pathogens is still controversial, several researchers have suggested that their secondary metabolites such as CLA might enhance their overall in vivo health-beneficial functions [14,2325]. Here in the current study, we systematically and in-depth investigated the double effects of both Lactobacillus and CLA on murine gut health.…”
Section: Discussionmentioning
confidence: 96%
“…Whereas, LC + mcra displayed more intensive reductions considering the extraneous strengthening effects implemented by its over-promoted CLA production [14]. In fact, CLA has been documented and linked with antimicrobial active against several enteric bacterial pathogens including Salmonella though the specific mechanism are still under study [23,37]. Most importantly, the in vivo examination based on BALB/cJ mice model justified the protective roles of LC + mcra on combating enteric bacterial pathogens, following and matching with previous in vitro outcomes relied on various pathogenic bacterial strains [20,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The cell pellets were then resuspended with sterile broth to the optical density of 0.05 at 600 nm (OD 600 ≈ 0.05). The subsequent experimental operation referred to Byeon’s method in a 96-well microtiter plate (41). The MIC was defined as the lowest GMM concentration which prevented bacteria growth for 24 h (48 h for C. albicans ) when the absolute value of the difference between the initial and final OD 600 was less than 0.05.…”
Section: Methodsmentioning
confidence: 99%